2017
DOI: 10.1597/15-019
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Chondrocutaneous Branchial Remnants

Abstract: A review of the literature revealed no evidence for sinuses or cysts related to cervical chondrocutaneous branchial remnants. Operative treatment can be postponed to a suitable and safe age. There is marked variation in the reported prevalence of associated anomalies, ranging from 11% to 76%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Tarmir et al suggested surgical treatment of CCBR just before starting school, which allows minimization of surgical complications and spares the child of the psychological complications; however, it can be postponed to a suitable and safe age. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Tarmir et al suggested surgical treatment of CCBR just before starting school, which allows minimization of surgical complications and spares the child of the psychological complications; however, it can be postponed to a suitable and safe age. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is complete surgical removal as promptly as possible to get an exact histopathological diagnosis [ 15 ]. If the patient involved is a pediatric, operative treatment can be postponed to a suitable and safe age [ 8 ]. Histopathological studies are then recommended, where investigations define this lesion as heterotopic, composed of normal skin and fat with a strip of cartilage running through the middle [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal ultrasound and cardiac examination are recommended because of possible associated anomalies [ 7 ]. These anomalies must be taken into consideration, as there is marked variation in the reported prevalence of associated anomalies, ranging from 11% to 76% [ 8 ]. Thus ultrasound, being the least invasive diagnostic technique, while also serving the patient with maximum utility, was the modality of choice.…”
Section: Case Presentationmentioning
confidence: 99%
“…Cervical chondrocutanous branchial remnants (CCBRs) are uncommon embryonic lesions that can occur unilaterally or bilaterally observed, A significant preponderance of men was previously observed, however Klockars et al discovered no gender propensity in a 2015 review [1]. The phrase "chondrocutanous branchial remnant" refers to the presence of heterotopic cartilage under the skin in the cervical area [2].…”
Section: Introductionmentioning
confidence: 99%